Ideologisasi Dakwah Digital: Analisis Wacana Kritis Postingan Hadis di Akun @Kajianislam - Ayatullah, Ayatullah; M Syam, Masiyan; Hatta, Juparno (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research is motivated by the rapid technological advancements of the modern era and their significant implications for socio-religious reality. The mediatization of religion shows that Islamic messages are now widely disseminated through social media. However, this dynamic has also led to fragmentation in religious understanding and authority. Often, hadiths are disseminated on social media to strengthen the position of certain groups in the social, political, or religious spheres. This study focuses on the dissemination of hadiths through social media, using the Instagram account @Kajianislam as a case study. The study employs a qualitative approach with a virtual ethnographic focus and is based on Teun A. van Dijk's critical discourse analysis theory for data analysis. The study's results show ideological construction in the presentation of hadiths on this account. First, text and visual elements are strategically used to reinforce the manhaj salaf ideological message. Second, the choice of diction and narrative in each post creates an understanding that aligns with the values of Manhaj Salaf. Third, the content produced on this account demonstrates an attempt to maintain group identity while instilling Islamic interpretations consistent with the promoted ideology. Thus, disseminating hadith on social media functions not only as a means of da'wah but also as a discursive practice that reproduces religious ideologies in the digital space.